Remarks on Pollen Representation of Mistletoe (Viscum album L.) - Noryśkiewicz, Agnieszka; Noryśkiewicz, Bożena (Ecological Questions, 2017)
Productivity and dispersal of mistletoe pollen (Viscum album L.) is discussed on the basis of its representation in fossil sediments (2 profiles representing the Holocene successions – one from Lake Strażym and one from Retno peatbog), moss samples (15 samples covering a period of 6 years), annual pollen monitoring data (19 years) and pollen amount in the flower and inflorescence investigation. The main question to be clarified is whether and how closely the moss samples reflect the presence of mistletoe. The results of the study have proved that even a single pollen grain may indicate the presence of a large Viscum population near the site.